Investigation of the use of Moringa Oleifera as dewatering aid - Jami, Mohammed Saedi; Muyibi, Suleyman Aremu; Baharom, Nur Amalina; Alam, Md. Monjurul (IIUM Press, International Islamic University Malaysia, 2017)
Moringa oleifera seed can be applied as a conditioner in sludge handling. In this study, sludge conditioning properties of Moringa oleifera seed were examined for kaolin suspension in aqueous media. The performance of the Moringa oleifera seeds as a sludge conditioner was evaluated for various seed preparations such as water extraction, salt extraction, oil extraction and water extraction and lastly oil extraction and salt extraction based on sludge settling velocity, sludge volume index (SVI) and cake moisture content value. Three factors, Moringa oleifera seeds concentration, mixing speed and contact time, were considered for conditioning. In addition, the use of polyaluminum chloride as a sludge conditioner was compared to Moringa oleifera seeds. Higher settling velocity, better sludge volume index (SVI) and less cake moisture content were resulted in the oil extraction and salt extraction seed preparation method than any other preparation methods. However, the mixing of polyaluminium chloride with kaolin slurry caused the higher settling velocity in comparison with the mixing of Moringa oleifera seeds.